Studi Kepustakaan Peran Khat Dalam Menunjang Kemahiran Kitabah - Ristiani Arnila; Sapuadi (PT. Hasba Edukasi Mandiri, 2025)
This article explores the role of Arabic calligraphy (khat) in supporting maharah al-kitabah as an essential aspect of Arabic language learning. This study employs a library research method by examining books, journals, and relevant literature on calligraphy and Arabic writing skills. The findings show that khat holds an important position in Islamic scholarly and cultural traditions and has developed through various historical periods, resulting in diverse calligraphic styles. In the context of writing skills, khat enhances the accuracy of letter forms, strengthens adherence to writing rules, and refines the aesthetic quality of written Arabic. Thus, khat contributes significantly to improving the quality of Arabic writing both linguistically and artistically, while also supporting the preservation of Islamic artistic heritage.